Gendered and gender-neutral character of public places in Algeria - Rahmani, Lyes; Messaoudene, Maha (Quaestiones Geographicae, 2021)
This article aims to determine whether Algerian public spaces are gendered or gender neutral and to deduce the place of women in this type of hedonistic aesthetic consumption space. A non-probability sample of 363 individ- uals allowed us to collect the necessary data on the basis of an experiential scale designed for Algerian public spaces. This scale offers us the possibility of measuring their spatial and phenomenal experiential tendency. In other words, it allows us to evaluate the potential of their sensorial, relational, emotional, cognitive, behavioural spaces, their urban environments and their spirits of the place. This scale has undergone the tests of reliability and validity laid down by Churchill. It has also undergone the latest generation confirmatory factor analysis (CFA) method. Due to the non-nor- mality of the sample distribution, we applied non-parametric tests in our analysis. The Mann Whitney U tests were used to calculate and compare the indices of spatial and phenomenal segregation of public places. The results revealed the gendered or gender-neutral nature of the three public places with their respective mapping. In the end, on the basis of the cultural dimensions of Hofstede, we were able to get to know the populations of the cities in our case studies that require urgent awareness-raising action. This promotes gender equality and especially the right of women to use and occupy hedonic public spaces without any conditions or prejudice.